Fabrication of mold parts using fused deposition modeling and vacuum casting / Ayaz Asif - Ayaz , Asif (2019)
Molding the part is a conventional technique that is highly adopted in industries to produce plastic & metallic parts. This huge demand urged to use several automated CNC machining processes (material subtraction technique) to produce mold parts that is fast and accurate. Nowadays a lot of research is being conducted to produce metal parts by sintering the powder or binding the resin using laser or UV light (rapid prototyping) but it seems very difficult to achieve required mechanical properties under cyclic loading so a combination of latest fused deposition modeling (FDM) and conventional vacuum casting processes are used to produce mold parts as these processes are accurate and reliable. This methodology adopted is designing the mold using Solidworks (drafting, creating partition surface, building core & cavity and tools splitting), printing using fused deposition modeling printer (CAM at highest resolution), casting the part (preparing slurry mixture, filling in conical flask containing part, vacuum to remove bubbles, curing, dewaxing and filling) and finishing (refining edges, sand blasting, grinding and polishing) to make it presentable. Part produced is being inspected using microscopy and surface roughness test to highlight the efficiency and drawbacks in this process. For that purpose, 3D Scanning using Sense Scanner is done to look at all the dimensional changes and compared with CAD Drawing, so this process is so far 70-80% accurate and can be improved further by using specialized equipment (accuracy in printing, machine-based casting like investment casting), choosing the suitable part & size as downsizing and uneven surface are difficult to grind and polish and selecting the right material (SS 420). This process can have an impact on several industries like Automotive, Plastic based industries and can be expanded to producing parts in investment casting for Aviation Industry with the requirement of mold